(untitled) (Discourse of Law and Administration, 2026)
This study is an analysis of current legal regulations in the area of the legal status of the audit committee of the municipal council, with a sentence on the scope of its control competences. The basic issue that is the subject of the conducted research is to determine the limits of control activities conducted by the audit committee, with particular emphasis on actions taken towards municipal commercial law companies. As part of the conducted analyses, the author tries to decide whether the legal regulations in this area are uniform and their interpretation is coherent and consistent.